Investigating the Influence of Alumina Additive Concentrations on specific Fuel Consumption and Exhaust Opacity in Biodiesel Fuel - Muh Abdillah; Nurhidayanti; Ariawan Bayu Wicaksono; Ishak (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
This study investigates the effect of alumina (Al2O3) nanoparticle additives on the performance and emission characteristics of B30 biodiesel fuel under various engine loads. Fuel samples of pure B30 and B30 blended with Al2O3 at concentrations of 30, 50, 70, and 90 ppm were tested using a 3.5 kW diesel engine. The evaluation focused on specific fuel consumption (SFC), and exhaust opacity at loads of 1, 5, and 9 kg. The results show that SFC generally decreased with increasing load, with the lowest values achieved at 90 ppm, indicating improved combustion efficiency. In terms of emissions, the addition of Al2O3 at 30–50 ppm significantly reduced opacity, with 50 ppm showing the greatest effect, particularly at high loads. However, higher concentrations such as 90 ppm tended to increase opacity due to nanoparticle agglomeration, which hinders homogeneous mixing and combustion. Overall, the optimal performance improvement was observed at 50 ppm for emission reduction and at 90 ppm for fuel efficiency, demonstrating the potential of Al2O3 nanoparticles as effective additives in biodiesel applications.